Value chain analysis of bio-coal business in Finland: Perspectives from multiple value chain members. (July 2015) - Wang, Lei
Abstract: The purpose of this study is to provide a comprehensive outline of the Value Chain (VC) 1 of bio-coal in Finland, define the proper business models of bio-coal business, and investigate the interrelationships between VC activities. The major findings are: 1) the study found significant interrelationships between support and primary activities in the bio-coal VC which suggest that we should not emphasis only the core value/primary activities of the bio-coal business, but pay more attentions to the "side values"/support activities; 2) The study identified political and environmental factors as the effective drivers, while technology and cost-profit uncertainty as major restrictions for the Finnish bio-coal business. The authors would like to suggest that instead of purely "environmental concerns", the term "sustainability credentials" should be emphasized, which means value creating and adding items should not limit to monetary values, but consider social and environmental value propositions. 3) The study identified "low competition" in the current bio-coal business in Finland, which implies opportunities of market entrance for Finnish and international companies; 4) The study identified that the current Finnish bio-coal model is the decentralized model at the local level. However, the future Finnish bio-coal model will be a large scaled model, with a focus on export sales. Highlights: Poters' VC analysis model. Significant interrelationships between support and primary activities. Emphasis on sustainability credentials. Low-competition in the current bio-coal business. Decentralized model.